1992
DOI: 10.1016/0378-1097(92)90231-c
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-mediated exchange of virulence determinants by co-cultivation of pathogenic Neisseriae

Abstract: The horizontal flow of genetic material between microbes utilizes three principal routes: conjugation, transduction and transformation. While the significance in nature of the first two pathways is generally accepted, the in vivo role of transformation remains uncertain, despite the early observations by Griffith in 1928 on the transformation of streptococci from an avirulent to a virulent state [1]. Recently, circumstantial evidence was collected suggesting a role for transformation-mediated horizontal exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Both isolates were characterized by ST3698 but they belonged to two different serogroups, C and B. Although capsular switching as a result of the horizontal transfer of siaD genes has been already described in N. meningitidis isolates in vitro and in vivo , this is the first report of capsule replacement in Polish meningococci (Frosch & Meyer, 1992; Swartley et al , 1997; Kertesz et al , 1998; Alcala et al , 2002; Stefanelli et al , 2003). It was not possible to establish the direction of the capsular switching, because even in this study we found the isolate of ST2177, a single variant locus of ST3698, with the phenotype B:NT:P1.6.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Both isolates were characterized by ST3698 but they belonged to two different serogroups, C and B. Although capsular switching as a result of the horizontal transfer of siaD genes has been already described in N. meningitidis isolates in vitro and in vivo , this is the first report of capsule replacement in Polish meningococci (Frosch & Meyer, 1992; Swartley et al , 1997; Kertesz et al , 1998; Alcala et al , 2002; Stefanelli et al , 2003). It was not possible to establish the direction of the capsular switching, because even in this study we found the isolate of ST2177, a single variant locus of ST3698, with the phenotype B:NT:P1.6.…”
Section: Discussionmentioning
confidence: 84%
“…Because there is no vaccine available against serogroup B meningococci, the C to B capsular switching may have a greater impact for public health, especially if it expresses the same epidemic potential as its serogroup C variant. The phenomenon of the capsule switching has been mostly reported after mass vaccination campaigns; however, it is also known that genetic variants of different serogroups may be produced randomly in a meningococcal population, independent of a vaccination pressure (Frosch & Meyer, 1992; Alcala et al , 2002). This may be the case in our study, because in Poland a mass vaccination against serogroup C meningococci was never implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation and recombination events influence expression of meningococcal capsule (Frosch&Meyer, 1992). Co-colonization of different serogroup strains in the human nasopharynx and genetic exchange of the cps gene clusters by transformation and allelic-exchange result in “capsule switching” in vivo (Swartley et al, 1997).…”
Section: Mechanisms Affecting Capsule Expressionmentioning
confidence: 99%
“…Thus, natural transformation accounts for the rapid exchange and adaptation of virulence factors [2] and antibiotic resistances [3] by generating mosaic genes [3-51, for the exhaustive linkage equilibrium of genetic markers within the N. gonorrhoeae population [6], and contributes as a mechanism of pilin variation to the remarkable structural and antigenic diversity of pili [7-91. The early description of transformation-deficient mutants by Biswas et al [lo] led to a dissection of the transformation process into two steps, a DNA uptake step whereby the transforming DNA is converted to a DNase-resistant state, and any subsequent events. Like many bacterial pathogens, N. gonorrhoeae is naturally competent for DNA transformation [ 11.…”
Section: Introductionmentioning
confidence: 99%